2020
DOI: 10.1016/j.bcp.2020.113869
|View full text |Cite
|
Sign up to set email alerts
|

S-nitrosylation affects TRAP1 structure and ATPase activity and modulates cell response to apoptotic stimuli

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 47 publications
(76 reference statements)
1
25
0
Order By: Relevance
“…Besides this regulation, it has also been very recently reported that S-nitrosylation of Cys501 produces a decrease of TRAP1 ATPase activity likely through an allosteric mechanism (Faienza et al, 2020). ATPase assays, together with molecular dynamics simulations, indicate that S-nitrosylation negatively impacts TRAP1 activity i) directly, through intra-and interprotomer long-range communication events that exert distal effects on the active site, and ii) indirectly, through the regulation of open-to-close state transition, which is crucial for this class of chaperones to complete the ATPase cycle (Faienza et al, 2020). Cells expressing a mutant form of TRAP1, in which Cys501 is substituted by a serine (C501S), are more resistant to mitochondrial toxins and to staurosporine-induced apoptosis (Faienza et al, 2020), suggesting that S-nitrosylation of Cys501 impacts TRAP1 biology.…”
Section: Trap1 Is a Target Of S-nitrosylationmentioning
confidence: 91%
See 1 more Smart Citation
“…Besides this regulation, it has also been very recently reported that S-nitrosylation of Cys501 produces a decrease of TRAP1 ATPase activity likely through an allosteric mechanism (Faienza et al, 2020). ATPase assays, together with molecular dynamics simulations, indicate that S-nitrosylation negatively impacts TRAP1 activity i) directly, through intra-and interprotomer long-range communication events that exert distal effects on the active site, and ii) indirectly, through the regulation of open-to-close state transition, which is crucial for this class of chaperones to complete the ATPase cycle (Faienza et al, 2020). Cells expressing a mutant form of TRAP1, in which Cys501 is substituted by a serine (C501S), are more resistant to mitochondrial toxins and to staurosporine-induced apoptosis (Faienza et al, 2020), suggesting that S-nitrosylation of Cys501 impacts TRAP1 biology.…”
Section: Trap1 Is a Target Of S-nitrosylationmentioning
confidence: 91%
“…ATPase assays, together with molecular dynamics simulations, indicate that S-nitrosylation negatively impacts TRAP1 activity i) directly, through intra-and interprotomer long-range communication events that exert distal effects on the active site, and ii) indirectly, through the regulation of open-to-close state transition, which is crucial for this class of chaperones to complete the ATPase cycle (Faienza et al, 2020). Cells expressing a mutant form of TRAP1, in which Cys501 is substituted by a serine (C501S), are more resistant to mitochondrial toxins and to staurosporine-induced apoptosis (Faienza et al, 2020), suggesting that S-nitrosylation of Cys501 impacts TRAP1 biology. Integrating these pieces of evidence, it is reasonable to propose that S-nitrosylation-induced degradation of TRAP1 is a direct consequence of its loss of activity.…”
Section: Trap1 Is a Target Of S-nitrosylationmentioning
confidence: 99%
“…The cysteine can change the conformation of TRAP1 during its catalytic cycle, as determined by molecular dynamics simulations (Faienza et al, 2020). It also enables the interaction with client proteins (Faienza et al, 2020). This PTM has an inhibitory effect on the ATPase activity, which is in line with the protective role of TRAP1 in apoptosis (Faienza et al, 2020).…”
Section: Modulation Of Trap1 Activitymentioning
confidence: 96%
“…PTMs play an important role in the regulation of TRAP1, including (de)acetylation, (de)phosphorylation, S-nitrosylation and ubiquitination (Table 1) (Anckar and Sistonen, 2011;Matassa et al, 2012;Faienza et al, 2020). Similar to HSP90, phosphorylation contributes to activation of TRAP1 (Trepel et al, 2010;Anckar and Sistonen, 2011).…”
Section: Modulation Of Trap1 Activitymentioning
confidence: 99%
See 1 more Smart Citation